EKSISTENSI SISTEM HUKUM PERIZINAN KEGIATAN PERTAMBANGAN DALAM OTONOMI DAERAH SEBAGAI SALAH SATU INSTRUMEN HUKUM HAK-HAK MASYARAKAT - Putra, David Aprizon (Legality : Jurnal Ilmiah Hukum, 2016)
Mining activity permit system would be the most urgent and most of its functions in maintaining the implementation of processing and protection of the environmental in Indonesia. For that purpose, it is expected the strengthening of the role of government, especially the local government as the owner of the mine producing areas. The ultimate goal of this course is for the benefit of mankind itself, society, state and nation of Indonesia. The permit system is desired able to preserve the rights of society as residents who has a wealth of space mining jurisdictions in general and the affected local communities in particular. After that the legality of permit system must have a strong substance of legal material used to be able to accommodate the interests and rights owned by the public. It is necessary to strengthen the quality of permits issued by the Regional Government in terms of safeguarding the rights of society-rich regions.